Boundedly rational opinion dynamics in social networks: Does indegree matter? - Pietro Battiston; Luca Stanca (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2015)
This paper investigates opinion dynamics and social influence in directed communication networks. We study the theoretical properties of a boundedly rational model of opinion formation in which individuals aggregate the information they receive from their neighbors by using weights that are a function of neighbors' indegree. We then present the results of a laboratory experiment explicitly designed to test the causal effect of indegree on social influence. We find that the social influence of an agent is positively affected by the number of individuals she listens to. When forming their opinions, agents take into account the structure of their communication network, although only to a limited extent.
Keywords: D85; D83; A14; L14; Z13; 330; Social Networks; Learning; Social Influence; Bounded Rationality